2023
DOI: 10.1186/s13568-023-01525-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and phylogenetic analysis of Enterococcus isolates using MALDI-TOF MS and VITEK 2

Abstract: The bacterial genus Enterococcus encompasses 38 species. Two of the most common species are E. faecalis and E. faecium. Recently, however, there has been an increase in clinical reports concerning less prevalent Enterococcus species, such as E. durans, E. hirae, and E. gallinarum. Rapid and accurate laboratory methods are needed to facilitate the identification of all these bacterial species. In the present study, we compared the relative accuracy of matrix-assisted laser desorption/ionisation time-of-flight m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The genus Enterococcus is ubiquitous in various habitats and currently comprises 38 species 18 . In this study, phylogenic trees of 16S rRNA gene sequences indicated that the rumen isolates are closely related to the species E. faecium and E. gallinarum with bootstrap values ranging from 92 to 99% (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Enterococcus is ubiquitous in various habitats and currently comprises 38 species 18 . In this study, phylogenic trees of 16S rRNA gene sequences indicated that the rumen isolates are closely related to the species E. faecium and E. gallinarum with bootstrap values ranging from 92 to 99% (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MALDI-TOF MS proved to be an accurate system for the identification of both usual and unusual Enterococci with a high level of species-level discriminatory power [ 3 ]. The low rate of E. hirae incidence may have been the consequence of the limited power of other diagnostic systems; indeed, the identification of E. hirae increased after the development of MALDI-TOF MS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Enterococci are a frequent cause of infection in humans, only 0.4% to 3.03% are reported to be from E. hirae species; nevertheless, these data may be underestimated due to its difficult isolation, and its identification could increase using MALDI-TOF: a diagnostic system with a higher sensitivity level compared to previous ones [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physiological and biochemical characteristics were determined using Vitek 2 compact 60 system [ 33 , 34 ] in this work.…”
Section: Methodsmentioning
confidence: 99%